Fraud Hexagon untuk Mendeteksi Indikasi Financial Statement Fraud - Cipta, Adriaan Togudo; Nurbaiti, Annisa (E-Jurnal Akuntansi; Vol 32 No 10 (2022)DO - 10.24843/EJA.2022.v32.i10.p06, 2022)
This study aims to analyze indications of fraud using the fraud hexagon in property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. The research population is 30 companies. The sample selection technique used purposive sampling technique, so that the total sample was 150 observations for the 5-year study period. The study used logistic regression analysis techniques with the help of SPSS version 26 for data processing. The results of the study prove that auditor turnover and political connections have an effect on financial statement fraud, while leverage, effective monitoring (BDOUT), change of directors, and the frequency of appearance of Chief Executive Officer (CEO) photos have no effect on financial statement fraud. Keywords: Pressure; Opportunity; Rationalization; Ability; Arrogance; Collusion; Fraudulent Financial Statements.